Nocturnal blue light exposure increase alpha and beta brain waves as cognition function for two consecutive night driving in a car simulator - Fitri, Lulu Lusianti; Prestiasani, Kinanti; Suprijanto, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Driving is a complex activity that engage complex motor, sensor, and cognitive function which can be analyzed through brain wave using electroencephalograph (EEG). Decrease of cognitive function while driving in long period at night linked with drowsiness and exposure of blue light to driver in night-driving could improve cognitive function; yet, studies describing its exposure in longer duration and repetition effects are needed. In this study, 15 adult males experienced driving session on the car simulator with a straight and monotonous road for 2 consecutive nights for 30 min without pause. The participants were divided into three driving groups as follows: in dark condition (control), under exposure to polychromatic blue light (450-540 nm) and monochromatic blue LED light (460 nm). All participants’ brain waves were recorded by EEG during the driving session from two channels of F3 and F4 representing cognitive function of the brain. The results showed that there was a significant increase of beta and alpha wave power spectral density on the second day of exposure in both blue light treatment groups. However, monochromatic blue light gave a more stable beta wave than the other two lights which indicate a much stronger cognitive process. There was also a synchronization from both channels of F3 and F4 in all treatments which shows that alpha and beta waves do not necessarily work in an antagonistic way. In summary, repeated, continuous exposure of blue light may increase alpha and beta wave power spectral density, in which monochromatic blue light causes better cognitive state than polychromatic blue light.